Pesan Implisit Anti Kolonial dalam Tema Peperangan Serat Centhini sebagai Cermin Kritis Masyarakat Jawa pada Abad ke-19 - Warda Firdausi Karimah; Reza Safitri (Musamus Journal of Public Administration, 2024)
Exploring the implicit anti-colonial message in Serat Centhini is an important and relevant effort. This is to investigate the extent of resistance to foreign influence and open views on how local literature and culture can be a strong tool in resisting and responding to socio-political changes facing society. The aim of this research is to determine the implicit anti-colonial message in the Serat Centhini war theme. This research adopts an interpretive approach using Gadamer's hermeneutical circle. Documentation techniques are applied for data collection. The analysis carried out includes narrative and phenomenological analysis. The research results show that Serat Centhini reflects the spirit of resistance and courage of the Javanese people in facing colonial domination. The author, who is strongly suspected to be Pakubuwana V, presents a postcolonial message that wants to restore the great dignity of Islamic Mataram in the face of Dutch and British colonialism. Not only through Serat Centhini, but also other works, such as the Rajamala Ship, became an astonishing tool of resistance against the invaders. Thus, Serat Centhini is not only a monumental literary work, but also a silent witness to the struggle and spirit of resistance of the Javanese people against colonial domination in the 19th century.